FERRIALLANITE-(CE), CACEFE3+ALFE2+(SIO4 (SI2O7)O(OH), A NEW MEMBER OF THE EPIDOTE GROUP: DESCRIPTION, X-RAY AND MöSSBAUER STUDY - Kartashov P.M.; Ferraris G.; Ivaldi G.; Sokolova E.; McCammon C.A. (My University, 2002)
Ferriallanite-(Ce), ideally CaCeFe3+AlFe2+(SiO4 (Si2O7)O(OH), is the analogue of allanite-(Ce) with Fe3+ dominant in the octahedral site M(1). It is of metasomatic origin and occurs in an alkaline granitic pegmatite of Mount Ulyn Khuren in the Altai Range (about 48°32′N, 92°55′E). Mongolian People's Republic. Ferriallanite-(Ce) is black, opaque or translucent, with a brown streak; the luster is resinous. The Mohs hardness is 6; it is brittle, without observed cleavage or parting. The fracture is conchoidal to uneven. Its density is 4.22 g/cm3. It is biaxial (-), α 1.825(2), β 1.855(5), γ 1.880(5), 2Vcalc 83°. The strongest five peaks in the X-ray powder-diffraction pattern [d(Å)(I) (hkl)] are: 2.93(65)(1̄13), 2.72(80 (120,013), 2.63(60)(3̄11), 2.18 (100)(122,1̄23,4̄01), 2.14(80 (221,4̄03,2̄23,014). The crystal structure has been refined to R = 0.026 using 2296 observed reflections collected with a four-circle X-ray diffractometer [a 8.962(2), b 5.836(2), c 10.182(2) Å, β 115.02(1)°. space group P21/m]. The position of the hydrogen atom has been found. On the basis of the chemical data, structure refinement, Mössbauer spectroscopy and charge- distribution calculations, the cations have been assigned to the independent crystallographic sites and the following crystal chemical formula has been obtained: (Ca0.97Ce0.03 (Ce0.89Ca0.11) (Fe3-0.80Ti4+0.14Al0.06 (Al0.56Fe3+0.44) (Fe2+0.93Mn0.07)(Si0.94 Al0.06O4)(Si2O7)O(OH). In the same sample, a single-point electron-microprobe analysis reveals an ideal composition CaCeFe3+2Fe2+(SiO4) (Si2O7)O(OH), but not enough material is available for a full characterization of this potentially new epidote-group mineral.
Keywords: ferriallanite-(Ce); new mineral species; crystal structure; Mössbauer spectroscopy; allanite subgroup; epidote group; alkaline granitic pegmatite; Altai Range; Mongolia